(untitled) (Research, Society and Development, 2023)
Systemic Arterial Hypertension (SAH) is defined as a chronic non-communicable disease characterized by elevated blood pressure levels, affecting over 1.2 billion people worldwide. It is an exceedingly costly condition for healthcare systems, involving both direct and indirect expenses. Given this context, it is feasible for healthcare systems to seek ways to prevent SAH and promote the health of hypertensive patients, contributing to cost reduction. Therefore, this article aims to analyze studies demonstrating the economic impact of pharmaceutical care on SAH management costs. The methodology adopted for this study was a narrative literature review, based on official documents and data from the Ministry of Health and DATASUS, as well as scientific materials from academic search platforms like Google Scholar, PubMed, and Scielo, spanning from 2010 to 2023. Based on these studies, it was evident that pharmaceutical assistance improved treatment adherence, reduced cardiovascular risks by 30.3%, and saved on hospitalizations, cardiology consultations, and emergency care costs. The annual investment of R 162.98 per controlled patient compared favorably to the R 117.55 spent on uncontrolled patients. Furthermore, patients monitored by pharmacists saved up to R 67.82 annually in healthcare costs. Consequently, it can be concluded that the integration of pharmaceutical care in hypertension has resulted in substantial economic and therapeutic benefits with broader social implications.